Performance Analysis of a VPV/FC Hybrid System for Generating Electricity in Iraq's Remote Areas - Z. Nawawi; A.S. Aziz; Z. Buntat; M.A.B. Sidik; H.J. Kareem; M.A.A. Aziz; A.Z. Abdulameer; M.I. Jambak; Y.Z. Arief (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
A reliable electrical energy supply is a prerequisite for improving the standard economic and quality of life levels in a country. As is the case in many countries, Iraq is home to a collection of remote villages. Since it is uneconomical to connect these villages to the existing grid, the installation of stand-alone electrical power generators has become common practice. As a result, diesel stand-alone power generators see widespread use in these remote locales, which, whilst fit for their intended purpose, unfortunately suffer from several drawbacks, including instability in regards to everyday oil prices and a number of environmental issues. The implementation of a PV/FC hybrid power system could be one potential alternative to help solve these problems. Therefore, this paper will present PV/FC system control strategies alongside information relating to the performance of such system components, based on a case study that was conducted in Al-Gowair, Iraq. This study is especially important in terms of envisioning the future energy supply needs of Iraq. The HOMER simulation results showed that by using the proposed control strategies and suggested components of a PV/FC system, it was able to produce a satisfactory outcome.